Occurrence and Pest Severity of Whitefly on Different Varieties of Chili - Nasrin, M; Amin, MR; Miah, MRU; Akanda, AM; Miah, GM (Annals of Bangladesh Agriculture, 2021)
Seasonal abundance, distribution and pest severity of white fly, Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) were studied on the chili (Capsicum spp.) varieties namely BARI Morich 1, BARI Morich 2, BARI Morich 3, BINA Morich 1 and Bogura Morich during November 2017 to June 2018 at Gazipur in Bangladesh. Results showed that the white fly started to build up their population from 2nd week of February on the chili varieties and exerted the peak abundance at the last week of February when the plants were at flowering stage. Abundances of white fly positively correlated with maximum temperature and relative humidity, and negatively correlated with minimum temperature and rainfall. Meteorological parameters predicted 11.6 to 32.9% abundance of whitefly on the chili varieties. Occurrence of white fly on different strata of the varieties was statistically low on BARI Morich 2 compared to other varieties. Virus infection levels among the varieties differed significantly and BARI Morich 2 showed the lowest level of infection. BARI Morich 2, Bogura Morich and BARI Morich 1 revealed low level of leaf curl indices (6.8 to 9.3%) and these varieties could be selected for cultivation in the areas where whitefly is a major pest of chili. Ann. Bangladesh Agric. (2020) 24(1) : 127-135